DIAGRAM ‘PROSES KEBUTUHAN – KEPUASAN KONSUMEN’ - Jajat Kristanto (President University, 2016)
Many authors of marketing textbooks explain concepts of need, want, demand, customer value, customer value migration, buyer or buying decision process, and customer satisfaction. However, and to my best knowledge, none of them describe the concepts in an integrated diagram. This paper tries to answer the challenge by offering an integrated diagram namely ‘Consumer Need – Satisfaction Process’ which explain the process starting from need recognition by consumers, become want and then demand for certain product category; the roles of marketers in persuading consumers to buy their products in order to satisfy their need; and, the satisfaction/dissatisfaction process experienced by consumers and its impact on others who demand the same product category. The paper also explains about value migration and how marketers must do in facing it